Peningkatan Hasil Dan Keaktifan Belajar Siswa Melalui NHT - Gebi Yustika; Erlina Prihatnani (Mathematics Education Study Program, 2019)
Inappropriate learning processes can lead to low learning results and student inactivity. This research (PTK) aims to improve learning outcomes and activeness of students in VIIH class of SMP Negeri 6 Salatiga students in rectangular and triangular material through Numbered Heads Together (NHT) learning application model. The model used in this research is Kemmis & Mc Taggart spiral model. It shows that the average result in the class is 64,4 (have not reach the minimum requirement) with percentage in passing the requirement of 46.40%. In cycle 2, the result increased with passing the average grade of 81.2 (fulfilling KKM) with percentage of 75% for passing grade requirement. Student activeness is increasing along with the learning outcomes. However, average category or high category on the 1st cycle is at 50,14%, while on the 2nd cycle, it can reach out to 80% or more. The two results concluded that implementing NHT could improve learning outcomes and activeness of students in VIIH class of SMPN 6 Salatiga.